Pengaruh Rasio Profitabiltas, Pertumbuhan, dan Ukuran terhadap Nilai Perusahaan - Civi Erikawati (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
This study purpose to determine the effect of Profitability Ratios, Growth and Size on Firm Value. The independent variables in this study are Return On Investment, Growth and Size. Meanwhile, the dependent variable is the Company Value which is proxied by Price Book Value (PBV). The sample used in this study were 104 manufacturing companies listed on the IDX. The analysis tested was using the classical assumption test consisting of normality test, autocorrelation test, multicollinearity test, and  heteroscedasticity test. Meanwhile, the hypothesis test is t test, F test, and R square. The results of this study can be concluded that the ROI, Growth and Size variables partially have an influence on the price book value. Based on the results of the F test, the ROI, Growth and Size variables simultaneously affect the price book value. Rsquare has a value of 0.566 which means 56.6% of the variable price book value can be explained by independent variables while the remaining 43.4% is explained by other factors.